2018
DOI: 10.1177/0268355518779844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulodexide on stability of sclerosing foams

Abstract: Background and objectives Foam sclerotherapy is a clinical procedure for the treatment of unhealthy veins. The aim of this study was to investigate the effect of sulodexide (SUL) on stability of foams prepared using polidocanol (POL) and sodium tetradecyl sulfate (STS) detergents, more specifically with 0.25% aethoxysclerol and 0.2% Fibro-Vein sclerosing solutions. Methods Foams were produced by the Tessari method using three different weight ratios of POL-SUL and STS-SUL (1:0, 1:1, and 1:3). Results The half-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Various nano- and micro-particles have been extensively researched for antimicrobial, anti-inflammatory, antioxidant, and anticancer effect [ 28 , 29 , 30 ]. Among them, the AgNPs are well known to have anti-bacterial and anti-inflammatory activities [ 22 , 23 , 24 , 28 , 29 , 30 ]. In our in vivo study, the degree of stent-induced tissue hyperplasia was significantly less in the AgNP-coated SEMS groups than in the control group at four weeks after stent placement, which correlated with the histological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Various nano- and micro-particles have been extensively researched for antimicrobial, anti-inflammatory, antioxidant, and anticancer effect [ 28 , 29 , 30 ]. Among them, the AgNPs are well known to have anti-bacterial and anti-inflammatory activities [ 22 , 23 , 24 , 28 , 29 , 30 ]. In our in vivo study, the degree of stent-induced tissue hyperplasia was significantly less in the AgNP-coated SEMS groups than in the control group at four weeks after stent placement, which correlated with the histological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency sweep measurements were then applied between 0.1 and 100 Hz by keeping the strain constant at 1% in order to obtain rheological parameters such as storage or elastic modulus (G′) and loss or viscous modulus (G″) of zein-based gels. Furthermore, the viscosity profiles of samples as a function of shear rate in the range of 0.1–100 s −1 were determined [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…176 In 2019, data showed that adding drugs such as sulodexide to polidocanol or sodium tetradecyl sulfate can even lead to a foam half-life prolongation. 177 A potential step-forward in foam sclerotherapy homogeneity has been offered by the non-physician-compounded polidocanol endovenous microfoam (Varithena V R ), whose efficacy and safety appeared to be equivalent or even better than physician-compounded foam. Nevertheless, the comparison was done against placebo and with only 1% concentration.…”
Section: Significant New Data Reported At the Meetingmentioning
confidence: 99%